Iodine deficiency disorders in a South Indian district: still a public health problem? - B. T., Prasanna Kamath; Bhattacharyya, Ananta; Mokhasi, Varsha R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Iodine deficiency disorders (IDD) constitute the single largest cause of preventable brain damage worldwide leading to learning disabilities and psychomotor impairment. Nearly 266 million school children worldwide have insufficient iodine intake. IDD was found to be a public health problem in 47 countries. Since the information on current prevalence of goiter in Kolar was not available, the present study was undertaken. Methods: A cross-sectional study was conducted among school children aged 6-12 years in Kolar taluk. A total of 2700 children were selected for goiter examination by multistage random cluster sampling technique. A total of 270 children were tested for the median urinary concentration and 540 salt samples were tested from the households of the study population. Results: The total goiter rate was 5.66% among primary school children aged 6-12 years with a significant difference between ages. As the age increased the goiter prevalence also increased. The median urinary iodine excretion level was found to be 105 mcg/l and 92.788.7% salt samples had >15 ppm iodine content. Conclusions: Present study shows mild goiter prevalence in primary school children in Kolar district and an adequate iodine content of salt in urine.